Validation of KREAM Based on In-Situ Measurements of Aviation Radiation in Commercial Flights - Junga Hwang; Jaeyoung Kwak; Gyeongbok Jo; Uk-won Nam (Journal of Astronomy and Space Sciences, 2020)
There has been increasing necessity of more precise prediction and measurements of aviation radiation in Korea. For our air crew and passengers’ radiation safety, we develop our own radiation prediction model of KREAM. In this paper, we validate the KREAM model based on comparison with Liulin observations. During early three months of this year, we perform total 25 experiments to measure aviation radiation exposure using Liulin-6K in commercial flights. We found that KREAM’s result is very well consistent with Liulin observation in general. NAIRAS shows mostly higher results than Liulin observation, while CARI-6M shows generally lower results than the observations. The percent error of KREAM compared with Liulin observation is 10.95%. In contrast, the error for NAIRAS is 43.38% and 22.03% for CARI-6M. We found that the increase of the altitude might cause sudden increase in radiation exposure, especially for the polar route. As more comprehensive and complete analysis is required to validate KREAM’s reliability to use for the public service, we plan to expand these radiation measurements with Liulin and Tissue Equivalent Proportional Counter (TEPC) in the near future.